Programme ERASMUS+ master degree industry 4.0 (IOT4.0) 2019-2022 - Chan, Margaret Kit Yok (UiTM Sarawak, 2021)
Universiti Teknologi MARA Sarawak Branch obtained a second European Commission ERASMUS + Capacity Building in Higher Education programme under grant agreement No 610455-EPP-1 -2019-1-MY-EPPKA2-CBHE-JP as a project leader. This project with an international cooperation for curriculum development Master Degree in Industry 4.0 (IOT4.0) 2019-2022 aims to provide practical solution so as to help closing the gap between industry needs/expectations and educational system outputs, in relation Industry 4.0 in the target countries. It involved the design ofMaster of Science curricula that promotes a shift from degree focused qualification to competence-based qualification.